Optimizing MSMEs: Google My Business Strategy to Increase the Visibility of Pematang Siantar MSMEs - Afandi, Ahmad; Abdullah Sani; Muhammad Arifin Lubis; Rahmayati (Ilin Institute, 2024)
The purpose of this study is to increase the business visibility of MSME actors in Pematang Siantar City through the use of Google My Business. The methods include identifying needs, preparing materials, recruiting trainers, conducting theoretical and practical sessions, and evaluating. Of the 40 participants, most had shops and stalls that could have been more optimal in online marketing. The activity results showed that the training increased participants' understanding and skills in digital marketing, especially using Google My Business. Evaluation involves participant feedback, measurement of results, and recommendations for improvement. This activity concludes that the training has succeeded in having a positive impact on MSME actors in Pematang Siantar City, improving their digital skills and providing recommendations for further training to be more effective.